2014
DOI: 10.1093/glycob/cwu005
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of oxidative burst by distinct β-glucan-binding receptors and signaling pathways in human peripheral blood mononuclear cells

Abstract: β-Glucans possess broad immunomodulatory properties, including activation of innate immune functions such as oxidative burst activity. The differential roles of complement receptor type 3 (CR3) and Dectin-1, the known β-glucan receptors, and their associated signaling pathways in the generation of oxidative burst induced by different physical forms of Saccharomyces cerevisiae-derived β-glucan were examined in human peripheral blood mononuclear cells (PBMC). In this study whole glucan particle (WGP) or immobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 55 publications
2
25
0
Order By: Relevance
“…Several studies in mice have established that dectin-1 is the most efficient β-glucan receptor on immune cells Li et al, 2011;Taylor et al, 2007;Willment et al, 2001Willment et al, , 2005, while recent studies in man have reported that CR3 is more important in these responses (Bose et al, 2014;van Bruggen et al, 2009). Domestic pigs as translational model have much to offer, since recent genome wide studies indicate that pigs are immunologically far closer to man than mice (Dawson et al, 2013;Mair et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies in mice have established that dectin-1 is the most efficient β-glucan receptor on immune cells Li et al, 2011;Taylor et al, 2007;Willment et al, 2001Willment et al, , 2005, while recent studies in man have reported that CR3 is more important in these responses (Bose et al, 2014;van Bruggen et al, 2009). Domestic pigs as translational model have much to offer, since recent genome wide studies indicate that pigs are immunologically far closer to man than mice (Dawson et al, 2013;Mair et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, although neutrophils in man express dectin-1, phagocytosis of β-glucans and β-glucan-mediated ROS production is here completely dependent on CR3 (van Bruggen et al, 2009). Interestingly, Bose et al (2014) demonstrated that human monocytes use distinct receptors (dectin-1 and CR3) for oxidative burst in response to different physical forms of β-glucans. CR3, a β2 integrin, is usually associated with complement function, but recognises an array of various ligands.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…A Houttuynia cordata pectic polysaccharide (HCP-2) with a linear chain of 1,4-linked ␣-D-galacturonic acid residues could increase the secretions of IL-1␤, TNF-␣, MIP-1␣, MIP-1␤ and RANTES in human peripheral blood mononuclear cells via TLR-4 mediated signaling . Bose et al (2014) reported that 1,3-linked ␤-d-glucans could activates innate immune functions via Dectin-1 and CR3 mediated signaling pathways. SR has been shown to be the pattern recognition receptor of fucoidan.…”
Section: Recognition Of Ljp-31 By Innate Immune Receptorsmentioning
confidence: 99%
“…Recent study conducted by Bose et al (2014) on yeast derived beta-glucans, showed that in human peripheral blood mononuclear cells (PBMC) dectin-1 was the receptor for whole glucan particle but CR3 was the one for immobilized soluble beta-glucan. Another in vitro study on porcine innate immune cells showed that CR3 served as main receptor for 6 different beta-glucans in porcine neutrophils.…”
Section: Cell Receptors Of Beta-glucansmentioning
confidence: 99%